Performance of a PTW 60019 microDiamond detector in a 1.5 T MRI-linac. (7th March 2018) - Woodings, S J; Wolthaus, J W H; van Asselen, B; de Vries, J H W; Kok, J G M; Lagendijk, J J W; Raaymakers, B W
Abstract: Accurate small-field dosimetry is critical for a magnetic resonance linac (MRI-linac). The PTW 60019 microDiamond is close to an ideal detector for small field dosimetry due to its small physical size, high signal-to-noise ratio and approximate water equivalence. It is important to fully characterise the performance of the detector in a 1.5 T magnetic field prior to its use for MRI-linac commissioning and quality assurance. Standard techniques of detector testing have been implemented, or adapted where necessary to suit the capabilities of the MRI-linac. Detector warmup, constancy, dose linearity, dose rate linearity, field size dependence and leakage were within tolerance. Measurements with the detector were consistent with ion chamber measurements for medium sized fields. The effective point of measurement of the detector when used within a 1.5 T magnetic field was determined to be 0.80 ± 0.23 mm below the top surface of the device, consistent with the existing vendor recommendation and alignment mark at 1.0 mm. The angular dependence was assessed. Variations of up to 9.7% were observed, which are significantly greater than in a 0 T environment. Within the expected range of use, the maximum effect is approximately 0.6% which is within tolerance. However for large beams within a magnetic field, the divergence and consequent variation in angle of photon incidence means that the microDiamond would not be ideal for characterising the profiles and it would not be suitable for determining large-field beam parameters such as symmetry. It would also require a correction factor prior to use for patient-specific QA measurements where radiation is delivered from different gantry angles. The results of this study demonstrate that the PTW 60019 microDiamond detector is suitable for measuring small radiation fields within a 1.5 T magnetic field and thus is suitable for use in MRI-linac commissioning and quality assurance.